Perubahan Osmolaritas Pasien Hiperglikemia dengan Terapi Rehidrasi - Erik Irham Lutfi (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2019)
Introduction: Uncontrolled DM hyperglycaemia will cause an increase in osmolarity which will disrupt the body's fluid and electrolyte balance. Rehydration therapy will replace the composition of body fluids caused by hyperosmolarity. Observation of management of hyperglycaemia only focuses on looking at blood sugar levels after rehydration therapy is given without looking at the body's osmolarity as an indicator of body fluid balance. This study aims to analyse changes in osmolarity in hyperglycaemic patients receiving rehydration therapy.Methods: This study was a comparative study with a prospective cohort approach. The number of samples in this study were 56 respondents with data collection using the consecutive sampling technique. Study sample of hyperglycaemic DM patients receiving rehydration therapy at the emergency room at a hospital in Tulungagung. The research instrument used an observation sheet. Data analysis used paired t-test.Results: Based on bivariate analysis there are changes due to rehydration therapy in the osmolarity variable with p value 0.000.Conclusion: Changes in osmolarity occur due to a decrease in blood glucose levels after fluid rehydration is carried out. This further proves that rehydration therapy is very effective in reducing blood glucose levels (hyperosmolarity) in the blood. Continuous osmolarity and hemodynamic examination are very necessary for hyperglycaemic patients with rehydration therapy to determine the effects of rehydration therapy as well as to determine the side effects of rehydration therapy so prevention can be done so that it does not become a problem causing emergency emergency situations.